Present Status and Future Prospects of Jute in Nanotechnology: A Review - Shah, Syed Shaheen; Shaikh, M. Nasiruzzaman; Khan, Mohd Yusuf; Alfasane, Md. Almujaddade; Rahman, Mohammad Mizanur; Aziz, Md. Abdul (Chemical record, 2021)
Nanotechnology has transformed the world with its diverse applications, ranging from industrial developments to impacting our daily lives. It has multiple applications throughout financial sectors and enables the development of facilitating scientific endeavors with extensive commercial potentials. Nanomaterials, especially the ones which have shown biomedical and other health‐related properties, have added new dimensions to the field of nanotechnology. Recently, the use of bioresources in nanotechnology has gained significant attention from the scientific community due to its 100 % eco‐friendly features, availability, and low costs. In this context, jute offers a considerable potential. Globally, its plant produces the second most common natural cellulose fibers and a large amount of jute sticks as a byproduct. The main chemical compositions of jute fibers and sticks, which have a trace amount of ash content, are cellulose, hemicellulose, and lignin. This makes jute as an ideal source of pure nanocellulose, nano‐lignin, and nanocarbon preparation. It has also been used as a source in the evolution of nanomaterials used in various applications. In addition, hemicellulose and lignin, which are extractable from jute fibers and sticks, could be utilized as a reductant/stabilizer for preparing other nanomaterials. This review highlights the status and prospects of jute in nanotechnology. Different research areas in which jute can be applied, such as in nanocellulose preparation, as scaffolds for other nanomaterials, catalysis, carbon preparation, life sciences, coatings, polymers, energy storage, drug delivery, fertilizer delivery, electrochemistry, reductant, and stabilizer for synthesizing other nanomaterials, petroleum industry, paper industry, polymeric nanocomposites, sensors, coatings, and electronics, have been summarized in detail. We hope that these prospects will serve as a precursor of jute‐based nanotechnology research in the future. Jute produces the second most common natural cellulose fibers and large amounts of jute sticks as a byproduct. The main chemical composition of jute fibers and sticks, which have a trace amount of ash content, are cellulose, hemicellulose, and lignin. This makes jute an ideal candidate for utilization in nanotechnology and this review presents its latest developments and future potentials in the area.